2020
DOI: 10.1039/c9ra07686g
|View full text |Cite
|
Sign up to set email alerts
|

Anionic azo dyes removal from water using amine-functionalized cobalt–iron oxide nanoparticles: a comparative time-dependent study and structural optimization towards the removal mechanism

Abstract: Efficient and selective removal of azo dyes from water by amine-functionalized-CoFe2O4 nanoparticles reliant on structural features such as size, charge, hydrophobicity/hydrophilicity, and S/C atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 74 publications
(125 reference statements)
0
10
0
Order By: Relevance
“… 10 Meanwhile, the adsorption capacities of the adsorbents in this study were similar to that of magnetic cobalt-iron oxide nanoparticles (CoFeNPs1/CoFeNPs2) for the removal of reactive orange 16. 15 However, several adsorbents have presented higher RR24 adsorption capacities than those of the biochars in this study, namely, CuFe 2 O 4 /activated carbon for the adsorption of acid orange 7, 54 Eucalyptus sheathiana bark biochar for the removal of methylene blue dye, 12 and Zr-based chitosan for the adsorption of Orange II. 4 The optimal solution pH for RR24 adsorption in this study was similar to those for the adsorption of various azo dyes reported in ref.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“… 10 Meanwhile, the adsorption capacities of the adsorbents in this study were similar to that of magnetic cobalt-iron oxide nanoparticles (CoFeNPs1/CoFeNPs2) for the removal of reactive orange 16. 15 However, several adsorbents have presented higher RR24 adsorption capacities than those of the biochars in this study, namely, CuFe 2 O 4 /activated carbon for the adsorption of acid orange 7, 54 Eucalyptus sheathiana bark biochar for the removal of methylene blue dye, 12 and Zr-based chitosan for the adsorption of Orange II. 4 The optimal solution pH for RR24 adsorption in this study was similar to those for the adsorption of various azo dyes reported in ref.…”
Section: Resultsmentioning
confidence: 62%
“… 4 The optimal solution pH for RR24 adsorption in this study was similar to those for the adsorption of various azo dyes reported in ref. 15 , where CoFeNPs1/CoFeNPs2 was used for the removal of reactive orange 16, and in ref. 4 , where Zr-based chitosan was utilized for the removal of Orange II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, any bands assigned as hydrogenation products from carbon dioxide were not observed, , and the intensity of the band assigned as adsorbed water molecules was almost at the same level before and after the treatments under the pressurized argon atmosphere, indicating that water splitting to hydrogen did not occur in the reaction system. Moreover, the bands assigned as other nitrogenous products (nitrite, nitrate, hydrazine, and other amides) were not also observed. These results suggested that there was negligible amount of the byproducts accompanied with production of urea. Figure shows the DR UV–vis-NIR spectra of the silica hollow spheres without/with various absorbents.…”
Section: Resultsmentioning
confidence: 95%
“…15,16 Recent studies have reported several biopolymer photocatalysts for the organic dye removal process. Methylene blue degradation also has been investigated, and various forms of biopolymer nanophotocatalysts such as ZnO nanoowers, 17 cellulose nanocrystals, 18 chitosan nanocomposite, 19,20 cellulose microbers, 21 chitosan microspheres, 22 nanoparticles, 23,24 nanosheets, 25 multi-walled nanotubes, 26 nanomaterials, 27 nanostructure compounds [28][29][30] and various forms of metal complexes such as trinuclear complexes, 31 binuclear complexes, 32 one-dimensional complexes, 33 and multifunctional complexes 34 have been effectively used in the degradation of dyes. However, there has hardly been any report on the application of biopolymer Schiff base complexes in the photocatalytic degradation of dyes.…”
Section: Introductionmentioning
confidence: 99%